Comparison natural spawning with artificial spawning In gold fish oranda (carassius auratus) - Herry Christian; Hamdan Alawi; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research on the Comparisson between natural spawning and artificial spawning in gold fish oranda (Carassius auratus) was conducted in February 2014 in the Fish Hatchery and Breeding Laboratory of the Faculty of Fisheries and Marine Sciences, University of Riau. The research was to compare the result between natural spawning and artificial substrate with result artificial spawning using injection with ovaprim 0,5 ml/kg body weight females; 0,2 ml/kg body weight males in gold fish oranda (Carassius auratus). The container used in this study was 6 unit fiber size 100x60x50 cm2 The method used is an experimental method or direct observation and than process spawning one unit sampel don’t in simultaneously because different maturity level gold fish oranda.The results treatment showed that is natural spawning better than artificial spawning in terms of index ovisomatic 12,2 % (IOS); fertilized rate 86,8 % (FR), hatching rate 91,1 % (HR), survival rate of 10 days old fry 97,9 % (SR).Keywords: Spawning, substrat, gold fish oranda (Carassius auratus)